A web-based analytical urban flood damage and loss estimation framework. (May 2023) - Alabbad, Yazeed; Yildirim, Enes; Demir, Ibrahim
Abstract: Information and communication technology serves a crucial role in communicating flood risk to various stakeholders and facilitating mitigation decisions. While studies extensively utilize flood inundation maps for communicating flood risks, there is a need to integrate a broad spectrum of physical vulnerability parameters into risk estimates. This research aims to build a publicly accessible web platform to analyze and estimate riverine flood-related damages using HAZUS and HEC-FIA damage functions. This framework will provide loss estimation for properties, business interruption, vehicles, bridges, and lives. The analysis is available for two scopes, including community and property. The community extent enables the user to explore socioeconomic flood information for several communities in the State of Iowa. In the property scope, the user can generate outcomes for the impacts of "what if" flood scenarios using user-provided data. The framework offers a guidance tool to help decision-makers with flood management, such as investigating mitigation interventions. Graphical abstract: Image 1 Highlights: Introduced a web application to help decision-makers for flood impact assessment. Application generates flood impact without install any software. Extensive case studies from Iowa communities integrated into the application. Application analyzes and visualizes flood impact at community and property-level. Updated HAZUS building inventory data improves accuracy for damage estimation.